Synthesis and characterization of low-toxicity N-caprinoyl-N-trimethyl chitosan as self-assembled micelles carriers for osthole - Hu XJ (Dove Medical Press, 2013)
Xiao-juan Hu,1,* Yang Liu,1,* Xiao-feng Zhou,2,3 Qiao-ling Zhu,1 Yong-yan Bei,1 Ben-gang You,1 Chun-ge Zhang,1 Wei-liang Chen,1 Zhou-li Wang,1 Ai-jun Zhu,1 Xue-nong Zhang,1 Yu-jiang Fan4 1Department of Pharmaceutics, College of Pharmaceutical Sciences, Soochow University, Suzhou, People's Republic of China; 2College of Radiological Medicine and Protection, Soochow University, People's Republic of China; 3Changshu Hospital of Traditional Chinese Medicine, Changshu, People's Republic of China; 4Department of Clinical Laboratory, Second People's Hospital of Akesu, Akesu, People's Republic of China *These authors contributed equally to this work Abstract: Novel amphiphilic chitosan derivatives (N-caprinoyl-N-trimethyl chitosan [CA-TMC]) were synthesized by grafting the hydrophobic moiety caprinoyl (CA) and hydrophilic moiety trimethyl chitosan to prepare carriers with good compatibility for poorly soluble drugs. Based on self-assembly, CA-TMC can form micelles with sizes ranging from 136 nm to 212 nm. The critical aggregation concentration increased from 0.6 mg · L-1 to 88 mg · L-1 with decrease in the degree of CA substitution. Osthole (OST) could be easily encapsulated into the CA-TMC micelles. The highest entrapment efficiency and drug loading of OST-loaded CA-TMC micelles(OST/CA-TMC) were 79.1% and 19.1%, respectively. The antitumor efficacy results show that OST/CA-TMC micelles have significant antitumor activity on Hela and MCF-7 cells, with a 50% of cell growth inhibition (IC50) of 35.8 and 46.7 µg · mL-1, respectively. Cell apoptosis was the main effect on cell death of Hela and MCF-7 cells after OST administration. The blank micelles did not affect apoptosis or cell death of Hela and MCF-7 cells. The fluorescence imaging results indicated that OST/CA-TMC micelles could be easily uptaken by Hela and MCF-7 cells and could localize in the cell nuclei. These findings suggest that CA-TMC micelles are promising carriers for OST delivery in cancer therapy. Keywords: N-trimethyl chitosan, micelle solubilization, antitumor activity